Who's badn ; Seeing the light ; Kontragapi [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Deals with Mark and Faye Quindoy's revelation of Michael Jackson's perversion and abuses to children. Judiel, the visionary claiming to see the Blessed Virgin and takes messages from her. A band called "Kontragapi" playing Philippine ethnic instruments was set up by U.P. Prof. Edru Abraham.